Effects of web-based mindfulness programs for cancer patients: integrative review of randomized clinical trials. (Research, Society and Development, 2022)
Objective: To analyze randomized clinical trials evaluating the effects of mindfulness-based processes offered over the internet, as a complementary treatment for patients with different types of cancer. Method: Specific search strategies were built for each database, with controlled and uncontrolled descriptors, Boolean operators and truncations. Searches for study selection were performed in the following databases: Pubmed / Medline, PsycoInfo, Web of Science and Clinicaltrials.gov. Results: 8 studies were included in the integrative review, 2 of which are still under development. A total of 714 specialists with a diagnosis of cancer of any type or location participated in the completed studies. Online investigations based on mindfulness evaluated in the included studies showed positive effects on relevant outcomes for patients' psychological health, such as anxiety, depression, mood, sleep, quality of life, stress, fatigue, post-traumatic growth, well-being, spirituality. Conclusion: Interventions based on mindfulness through the internet have if there are promising therapies for health promotion with a focus on quality of life and reduction of psychological distress.